ANALISIS PENERAPAN HALAL VALUE CHAIN PADA USAHA MIKRO, KECIL DAN MENENGAH DI KABUPATEN SUMBAWA - U Usman; A Adeliah (Pusat Riset dan Publikasi, 2025)
This study aims to know the Implementation of Halal Value Chain in Micro, Small and Medium Enterprises (Study at Miiq Bakery Store). The type of this study was descriptive study. The type of data used was qualitative data. The sources of data in the study were primary and secondary data. The numbers of informants were 5 informants consisted of 1 key informant and 4 main informants. The tools used to collect data were interviews and observations. The technique of data analysis was the theory of Miles and Huberman which consists of data collection, data reduction, data presentation and drawing conclusions. The results of the study showed that each value chain activity of the Miiq Bakery store hadexcellence from its each portions, it was based that each of activities chain of activitiestotally tries to implemented Islamic values ??both of main and supporting activities. However, the result of this study showed that the activities of halal value chain had not been fully implemented optimally at the Miiq Bakery Store, it was because the Miiq Bakery Store did not yet had offline store, so that the fulfillment of direct evidence (Tangibles) for consumers could not be provided so that the activities of the Miiq Bakery store had not implemented the halal value chain perfectly.